802.3cn-2019 - IEEE Standard for Ethernet. (IEEE, 2019)
This amendment to IEEE Std 802.3-2018 adds Physical Layer (PHY) specifications and management parameters for 50 Gb/s, 200 Gb/s, and 400 Gb/s operation over single-mode fiber with reaches of at least 40 km.
Keywords: Ethernet (Local area network system); Fiber optics.